Fabrication of slippery liquid-infused porous surfaces for anti-fouling applications. (30th April 2021) - Atthi, Nithi; Suwan, Mantana; Sangwong, Nuchjarin; Pattamang, Pattaraluck; Sripumkhai, Witsaroot; Meananeatra, Rattanawan; Saengdee, Pawasuth; Thongsook, Oraphan; Ranron, Norabadee; Pankong, Krynnaras; Uahchinkul, Warinrampai; Jeamsaksiri, Wutthinan; et al.
Abstract: Lubricant-infused textured surfaces have gained much attention as liquid-repellent surfaces owing to high surface stability compared to their superhydrophobic counterparts. In this study, polydimethylsiloxane (PDMS) micro-structures (width: 20 μ m, height: 80 μ m), were fabricated using soft lithography. Effects of micro-structural geometry, including pillar-type (pillar, discrete ridge) and hole-type (hole, continuous ridge, circular rings with eight stripe supporters), on infiltration capability of the lubricants with different viscosity (Krytox-103; η : 0.131 Pa.s, Krytox-105; η : 0.737 Pa.s, paraffin oil; η : 0.112 Pa.s) were investigated. Partial infiltration was observed on the pillar-type micro-structures, while more completed infiltration was obtained on the hole-type micro-structures. More viscous Krytox-105 resulted in completed infiltration for all micro-structures, thus creating a slippery liquid-infused porous surface (SLIPS). The best SLIPS, signified by a low sliding angle and a fast speed of water droplet, prepared from the hole pattern infused with Krytox-105 exhibited good anti-fouling performance against chlorophyll and milk yogurt.